Hepatotoxicity And Lipid Profile Assessment Of Gardenia Jasminoides In Rats - Raphael Ogba (CV Media Inti Teknologi, 2025)
This study examined hepatotoxicity and lipid profile in the liver of rats treated with Gardenia jasminoides leaf extract. Ten healthy adult male albino rats were divided into two experimental groups: Group A (control given distilled water and commercial feed) and Group B given a certain concentration of Gardenia jasminoides leaf extract and commercial feed. The rats were euthanised on day 30, and blood samples were collected for further serum analysis. Livers were evacuated and weighed, and serum samples were sent to the Nigerian University Teaching Hospital for Lipid Profile Analysis. The results showed no significant decrease in organ/body weight ratio in the treated rats. Liver enzyme test results showed an increase in ACP, AST, and ALP activities, while a slight decrease was noted for ALT activity. Lipid profile analysis showed no significant decrease in HDL, but there was a significant decrease in LDL and TC. However, there was a significant increase in TG. Liver Enzyme Test and Lipid Profile Analysis in control and treated rats revealed that Gardenia jasminoides extract had positive effects on selected liver enzymes and lipid profile of treated rats. In conclusion, Gardenia jasminoides extract is neither toxic nor hepatotoxic to the liver, but rather a hepatoprotective agent.